Nanoscale Nickel–Chromium Powder as a Catalyst in Reducing the Temperature of Hydrogen Desorption from Magnesium Hydride; Hydrogen; Vol. 6, iss. 4 - Kenzhiyev A. Alan; Kudiyarov V. N. Victor Nikolaevich; Spiridonova A. A. Alena Aleksandrovna; Terentjeva D. V. Darjya Vitaljevna; Vrublevsky D. B. Dmitry Borisovich; Svyatkin L. A. Leonid Aleksandrovich; Nikitin D. S. Dmitry Sergeevich; Kashkarov E. B. Egor Borisovich (2025, 2025)
Title screen